Reading Objectives and Measurement Specifications, 1986-1990. Grade 1. Texas Educational Assessment of Minimum Skills (TEAMS) - Texas Education Agency, Austin. Div. of Educational Assessment; Texas Education Agency, Austin. Div. of Educational Assessment ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
The reading objectives and the measurement specifications cited in this document are congruent with the Texas State Board of Education Rules for Curriculum. The objectives are provided for teachers and for test developers involved with the preparation of the Texas Educational Assessment of Minimum Skills (TEAMS) tests. As of 1985-86 academic year, the TEAMS reading tests for first grade are based on the following objectives: (1) identify the main idea; (2) recognize words by sight; (3) recognize the meaning of compound words; (4) use context to understand the meaning of words; (5) use structural analysis to recognize root words; (6) recognize words through phonic analysis; (7) identify specific details, (8) identify the sequence of events; and (9) predict probable future outcomes. For each objective, this document provides a description of the test questions, a description of the answer choices and an example test question. (JAZ)
ERIC Note: For related documents, see TM 870 046-048.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Basic Skills; Behavioral Objectives; Educational Assessment; Grade 1.; Minimum Competency Testing; Primary Education; Reading Skills; Reading Tests; State Programs; State Standards; Test Format; Test Items; Testing Programs; Test Specifications -- Texas Educational Assessment of Minimum Skills; Guides, Non-Classroom.